Justified Restrictions of Property Rights in Practical Activity of the European Court of Human Rights and the Court of Justice of the European Communities - P. O. Kirienkov (Московский журнал международного права, 2010)
The article reviews approaches of the European Court of Human Rights and the Court of Justice of the European Communities to the problem of justified interference by a public authority with property rights. Operational procedures of the European law allow the mentioned interference. Even more according to the requirements of the principal of «good governance» the government should take all necessary measures for advocacy of public interest. At the same time to meet the regulations of the Convention for the Protection of Human Rights and Fundamental Freedoms the national government acts should comply with the principals, as follows: lawfulness, advocacy of public interest and proportionality. Content analysis of each of the mentioned principals, as an example of the recent years’ court practice is a strategic or key point.